The Influence of Creativity, Promotion, Productivity, and Price on the Demand for UKM Products (Songket Weaving) in Batu Bara Regency in the Islamic Economic Perspective - Yena Puspita; Muhammad Arif; Nurul Jannah (LPPM UIKA Bogor, 2023)
This study aims to determine the effect of creativity promotion productivity and price on the demand for songket weaving sma and medium enterprises (UKM) in the Batu Bara district from an Islamic economic perspective. This study used quantitative and descriptive methods with data collection techniques using questionnaires and the population and sample in this study were 73 songket weaving employees at Batu Bara. Data were analyzed using the multiple linear regression method with the help of SPSS IBM 26. The results of this study indicate that creativity has a significant effect on product demand for songket weaving small and medium enterprises (UKM), the promotion has a significant effect on product demand for small and medium enterprises (UKM) weaving songket productivity has no significant effect on the demand for songket woven small and medium enterprises (UKM), and prices do not affect the demand for songket woven small and medium enterprises (UKM) in Batu Bara district. And the results of the F test (Simultaneous Test) show that creativity promotion productivity and price simultaneously influence the demand for songket woven small and medium enterprises (UKM).